siRNAs from an X-linked satellite repeat promote X-chromosome recognition in Drosophila melanogaster - Menon, Debashish U.; Coarfa, Cristian; Xiao, Weimin; Gunaratne, Preethi H.; Meller, Victoria H. (Proceedings of the National Academy of Sciences - PNAS, 2014)
Significance Modulation of X-linked gene expression is essential in organisms with XX females and XY males. Various strategies for global regulation of X chromosomes have been proposed, but all require highly selective recognition of X chromatin. How this is achieved is not understood. The siRNA pathway contributes to X recognition in a well-studied Drosophila model. We now show that ectopic production of siRNA from a repetitive sequence that is limited to the X chromosome also promotes X recognition. Differential activities of X-linked repeats suggest a control region model, in which siRNA produced by a few repeats acts on widely distributed X-linked target sequences to promote selective recognition, and modification, of a single chromosome. Highly differentiated sex chromosomes create a lethal imbalance in gene expression in one sex. To accommodate hemizygosity of the X chromosome in male fruit flies, expression of X-linked genes increases twofold. This is achieved by the male- specific lethal (MSL) complex, which modifies chromatin to increase expression. Mutations that disrupt the X localization of this complex decrease the expression of X-linked genes and reduce male survival. The mechanism that restricts the MSL complex to X chromatin is not understood. We recently reported that the siRNA pathway contributes to localization of the MSL complex, raising questions about the source of the siRNAs involved. The X-linked 1.688 g/cm ³ satellite related repeats (1.688 X repeats) are restricted to the X chromosome and produce small RNA, making them an attractive candidate. We tested RNA from these repeats for a role in dosage compensation and found that ectopic expression of single-stranded RNAs from 1.688 X repeats enhanced the male lethality of mutants with defective X recognition. In contrast, expression of double-stranded hairpin RNA from a 1.688 X repeat generated abundant siRNA and dramatically increased male survival. Consistent with improved survival, X localization of the MSL complex was largely restored in these males. The striking distribution of 1.688 X repeats, which are nearly exclusive to the X chromosome, suggests that these are cis -acting elements contributing to identification of X chromatin.